2012
DOI: 10.1002/ajh.23308
|View full text |Cite
|
Sign up to set email alerts
|

Cytarabine and clofarabine after high‐dose cytarabine in relapsed or refractory AML patients

Abstract: Clofarabine has been shown to be effective in AML patients, either as single agent or, mainly, in association with intermediate dose cytarabine. Based on these reports, we conducted a preliminary study combining clofarabine and intermediate dose cytarabine in AML patients who relapsed or failed to respond to at least two induction therapies. We treated 47 patients affected by relapsed/refractory AML with a regimen including clofarabine at 22.5 mg/m2 daily on days 1–5, followed after 3 hr by cytarabine at 1 g/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Investigators have examined clofarabine's role in relapsed or refractory AML in multiple phase I-II studies and a single randomized controlled trial [6]. The ranges for overall response and complete response rates assessing the combination of clofarabine with cytarabine are 40-61% and 24-46%, respectively [5,[7][8][9][10][11][12]. The largest trial of clofarabine to date in the relapsed/refractory setting, CLASSIC I, was the only randomized controlled trial of this agent in the AML setting: in CLASSIC I, the combination of clofarabine and cytarabine was associated with overall and complete response rates of 47% and 35%, respectively, compared to 22% and 18% with cytarabine monotherapy.…”
Section: Clofarabinementioning
confidence: 98%
“…Investigators have examined clofarabine's role in relapsed or refractory AML in multiple phase I-II studies and a single randomized controlled trial [6]. The ranges for overall response and complete response rates assessing the combination of clofarabine with cytarabine are 40-61% and 24-46%, respectively [5,[7][8][9][10][11][12]. The largest trial of clofarabine to date in the relapsed/refractory setting, CLASSIC I, was the only randomized controlled trial of this agent in the AML setting: in CLASSIC I, the combination of clofarabine and cytarabine was associated with overall and complete response rates of 47% and 35%, respectively, compared to 22% and 18% with cytarabine monotherapy.…”
Section: Clofarabinementioning
confidence: 98%
“…GCLAC—Clofarabine is a second-generation deoxyadenosine analog that is characterized by high resistance to phosphorolytic cleavage by bacterial purine nucleoside phosphorylase, potent inhibition of DNA synthesis, prolonged retention of clofarabine triphosphate in leukemic blasts [ 34 ] and, similar to fludarabine and cladribine, can inhibit RNR reductase and increase the intracellular concentration of ara-CTP when administered prior to cytarabine [ 94 ]. Studies evaluating clofarabine with intermediate-dose cytarabine (1 gm/m 2 ) have found CR rates 35%–51% [ 33 , 34 , 35 ] ( Table 1 ). GCLAC is a regimen containing clofarabine, high dose cytarabine (2 g/m 2 ), and G-CSF that has resulted in comparable CR rates (46% in a phase I/II study) [ 36 ] ( Table 1 ).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%
“…As salvage chemotherapy outcomes for patients with PRD are dismal, there is accumulating evidence to suggest that HSCT with active disease is a viable strategy that consistently leads to a long-term OS of approximately 20% with studies identifying multiple prognostic factors (Table 3) 3-year OS for all patients was 19% with the following relevant risk factors on multivariate analysis: complete remission less than 6 months (for those without PRD), circulating blasts, nonhuman leukocyte antigen identical sibling donor, Karnofsky performance status less than 90%, and poor-risk cytogenetics. Given the increased efficacy of Clo in the salvage setting and tolerability in an elderly population [39,40,41 & ,55,58,59 & ], it has generated interest as conditioning chemotherapy prior to allogeneic HSCT. Utilization of this prognostic scoring system was subsequently externally validated in a large cohort of Italian patients [50 && ] that also included patients receiving reduced-intensity conditioning regimens or cord blood as a stem cell source.…”
Section: What Is the Role Of Hematopoietic Stem Cell Transplant?mentioning
confidence: 99%